Impact of treatment attendance on mental health outcomes within task-shared psychological treatments: a causal analysis from the PRIME India study - Saloni Dev; John Griffith; Collette Ncube; Vikram Patel; Alisa Lincoln (Cambridge Prisms: Global Mental Health)
Task-shared psychological treatments play a critical role in addressing the global mental health treatment gap, yet their integration into routine care requires further study. This study evaluated the causal association between an implementation factor of a task-shared psychological treatment and participant outcomes to strengthen the implementation-to-outcome link within global mental health. This secondary analysis utilized cohort data from the Program for Improving Mental Health Care (PRIME) implemented in Sehore, India where trained non-specialist health workers delivered treatment for depression and alcohol use disorder (AUD). Propensity scores and inverse probability of treatment weights examined the impact of mental health service users’ treatment attendance on users’ symptom severity (PHQ-9 scores for depression; AUDIT scores for AUD) at 3 and 12-month follow-ups. Among the 240 patients with depression, higher treatment session attendance led to 1.3 points lower PHQ-9 scores (vs. no attendance) and 2.4 points lower PHQ-9 scores (vs. low attendance) at 3 months, with no significant effects at 12 months. Among the 190 AUD patients, treatment session attendance did not have a significant impact on AUDIT scores. Our findings have implications for enhancing treatment session attendance among those with depression within task-shared psychological treatments.